Chemical Abundances in the Carina dSph Galaxy - Smecker-Hane, T. A.; Mandushev, G. I.; Hesser, J. E.; Stetson, P. B.; Da Costa, G. S.; Hatzidimitriou, D. (1999)
We report on the chemical abundances of stars in the Carina dwarf spheroidal galaxy (dSph) derived from low-resolution spectra. We have determined values of [Fe/H] for 52 stars from the reduced equivalent width of the Ca II infrared triplet lines. The Carina dSph has a mean metallicity of [Fe/H] = -1.99 +/- 0.08 and an intrinsic metallicity dispersion 0.25 dex (1 sigma). By directly determining the chemical abundances of Carina stars through spectroscopy, we can overcome the age-metallicity degeneracy inherent in color-magnitude diagrams (CMDs) and determine its star-formation history with unprecedented accuracy.
Keywords: Astrophysics